The administration of coriander essential oil and the intensity of nausea and vomiting in first trimester pregnant women at PMB Rismala Siagian Sei Halim Hasak Hamlet II year 2023 - Pohan, Atika; Jahriani, Nani; Tanjung, Nurlela (Science Midwifery, 2024)
Background: Pregnancy is a natural process that involves physiological changes during pregnancy, resulting in changes in the mother's organ systems including the endocrine and gastrointestinal systems, leading to nausea and vomiting, which are common sources of discomfort in pregnant women. Research Objective: To determine the effect of coriander essential oil aromatherapy on the intensity of nausea and vomiting in first-trimester pregnant women at PMB Rismala Siagian in Sei Halim Hasak Hamlet II Village in 2023. Method: Quantitative with a one-group pretest-posttest design. The study population consisted of 30 first-trimester pregnant women experiencing nausea and vomiting at PMB Rismala Siagian in Sei Halim Hasak Hamlet II Village. Sampling was done using total sampling. Data collection used questionnaires and observation sheets. Data analysis used the Wilcoxon test. Results: The hypothesis was accepted because the data analysis resulted in a p-value of 0.000 or p <0.05. Conclusion: There is an effect of coriander essential oil aromatherapy on reducing the intensity of nausea and vomiting in first-trimester pregnant women.